Information support of complex improving of security at the enterprise level - Evtushenko, Olga; Khalmuradov, Вatyr; Volodchenkova, Natalia (My University, 2013)
In this article is shown a great need in creation automated information system – The State Register of victims which were injured during work or have got occupational diseases. Being built on the base of conceptual reasoning of the main tasks, structure and functions and also thanks to modern information systems, the Register gives a chance to follow the cause-and-effect relationships and to control the risks of injury during work. The program «Analysis_of_accidents 1.0» is developed for registration accidents and injuries in production according to the reports of form H-1 and it was built in C++.
Keywords: injuries at work; accidents; information system; risk; виробничий травматизм; нещасний випадок; інформаційна система; ризик; производственный травматизм; несчастный случай; информационная система; риск; кафедра екології та екоменеджменту